2020
DOI: 10.1111/nph.16710
|View full text |Cite
|
Sign up to set email alerts
|

NRT2.1 C‐terminus phosphorylation prevents root high affinity nitrate uptake activity in Arabidopsis thaliana

Abstract: In Arabidopsis thaliana, NRT2.1 codes for a main component of the root nitrate high-affinity transport system. Previous studies revealed that post-translational regulation of NRT2.1 plays an important role in the control of root nitrate uptake and that one mechanism could correspond to NRT2.1 C-terminus processing. To further investigate this hypothesis, we produced transgenic plants with truncated forms of NRT2.1. This revealed an essential sequence for NRT2.1 activity, located between the residues 494 and 51… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 80 publications
1
31
0
Order By: Relevance
“…In the study of Jacquot et al . (2020), data obtained by native gel electrophoresis suggested that also NRT2.1 and NAR2.1 interact in high‐molecular‐weight oligomeric complexes, the largest of which was detected at c . 480 kDa.…”
Section: Figmentioning
confidence: 96%
See 4 more Smart Citations
“…In the study of Jacquot et al . (2020), data obtained by native gel electrophoresis suggested that also NRT2.1 and NAR2.1 interact in high‐molecular‐weight oligomeric complexes, the largest of which was detected at c . 480 kDa.…”
Section: Figmentioning
confidence: 96%
“…Jacquot et al . (2020) add to this understanding by elucidating a molecular mechanism that inactivates NO 3 − uptake, presumably to protect the plant against over‐accumulation of this important nutrient.…”
Section: Figmentioning
confidence: 99%
See 3 more Smart Citations